Effects of job embeddedness, faculty identity, burnout, and organizational traits on job satisfaction in university professors - Lee, Suk Yeol; Lee, Ho Seub (Edelweiss Applied Science and Technology, 2025)
This study examines the impact of job embeddedness, faculty identity, burnout, and organizational traits on the job satisfaction of university professors. It investigates general trends in job embeddedness, faculty identity, burnout, and job satisfaction, and examines the relationships among these variables. Additionally, the paper analyzes how professors’ characteristics, backgrounds, and psychological factors—such as job embeddedness, faculty identity, and burnout—affect their job satisfaction. Data were gathered from 27 universities, chosen based on region and size, with 236 out of 247 survey responses used for analysis. Findings indicate that while burnout levels were somewhat elevated, professors generally had positive insights regarding their faculty identity, job embeddedness, and job satisfaction. Positive correlations were found between faculty identity, job embeddedness, and job satisfaction, while burnout exhibited a negative correlation. These results suggest that strengthening faculty members’ identification with their roles and fostering a stronger sense of institutional embeddedness may reduce burnout and enhance job satisfaction.